Principles of estimating soil moisture parameters in the basin. - Yavkin, Vyacheslav; Khodan, Halyna (Iasi, 2022)
In the vertical structure of the river basin, the dominant formation is the soil. Conditions for the transformation of water supply to the surface of the basin are determined by the ability of the soil to give or, contrarily, retain a significant proportion of precipitation. The soil column in the process of formation of the flood hydrograph performs the functions of moisture transfer by two opposite signs of the vertical component: filtration and evaporation. The laws of infiltration were considered by us in the previous section, where it was found that the leading parameter of the infiltration process in addition to the intensity of rain is the filtration coefficient
Keywords: Key words: Infiltration, particle size distribution, soil moisture, porosity, filtration coefficient